The narrative of Jesus’ baptism and its reception in the worship of the Church - Gkutziudēs, Moschos 1975- (2020)
The article presents the effect that the various elements of the four versions of the narrative of Jesus’ baptism had on the worship of the Church. In particular, the elements which are mentioned are on the one hand, the ones that were used by the worship of the Church and on the other hand, the new facts which, though they are not in the Gospel, were incorporated into ceremonial practices during their evolution. We study the choice of narration as a liturgical reading in the Orthodox Church, its position in the Christian calendar, the connection of the baptism of Jesus with the baptism of the Christians, the theological connection to the death of Christ, the importance of the Jordan River for the Christian world and lastly, the theme of Jesus’ baptism in the Christian art of the early centuries.
Keywords: Jesus’s Baptism; History of Reception; Hermeneutics; Worship; firstChristians; Jordan River